PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATAN HASIL BELAJAR IPA SISWA KELAS IV SDN 006 PETONGGAN KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Samri '; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Abstract: Based on the observation in SDN 006 Petonggan, the place where the observer teaches, in learning process the teachers still use the old teaching process The consequence is the low of students’ outcome under the standard score (KKM So that it needs the change of learning process in which students feel what they are learning are important and hard to forget it even the process has passed.This research is the follow-class research as much as two cycles which each cycle consists of planning, implementation and observation, and reflection. The data taken of this study uses abservation and test technique.The result of this research shows that teachers’ activites on cycle I 75,00% and it increases on cycle II 89,28%. Students’ learning process also increase. On cycle I students’ activities reach 71,14% and on cycle II it becomes 92,85%. While the students’ learning outcome on cycle I 42,11% and on cycle II it increases to 84,21%.The conclusion taken from this research is the implementation of contextual teaching and learning model can increase the first grade students’ outcome in science subject of environment theme n SDN 006 Petonggan. Keywords: model contextual teaching and learning, Learning Outcame IPA